Lagrangian reduction of discrete mechanical systems by stages - Fernández, Javier (2016)
In this work we introduce a category of discrete Lagrange{Poincare systems £ β d and study some of its properties. In particular, we show that the discrete mechanical systems and the discrete dynamical systems obtained by the Lagrangian reduction of symmetric discrete mechanical systems are objects in We introduce a notion of symmetry group for objects of £ βd as well as a reduction procedure that is closed in the category Furthermore, under some conditions, we show that the reduction in two steps (first by a closed normal subgroup of the symmetry group and then by the residual symmetry group) is isomorphic in LPd to the reduction by the full symmetry group.